Association between non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio and sarcopenia in individuals with cancer: a cross-sectional study - He, Ran; Ye, Youjun; Zhu, Qilei; Xie, Changsheng (Lipids in health and disease, 2024)
Cancer and sarcopenia are both closely related to lipid metabolism, but the relationship between lipid metabolism and patients with cancer and sarcopenia has not been thoroughly studied. The non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio (NHHR) is a reliable measure of lipid metabolism. The purpose of this study was to determine the possible relationship between the NHHR and sarcopenia in individuals with cancer. Data from the National Health and Nutrition Examination Survey (NHANES) database for individuals with cancer, with and without sarcopenia was analyzed using weighted multiple regression equations, weighted regression cubic spline (RCS) analysis, and weighted subgroup analysis. In total, 1,602 individuals with cancer were included, of whom 17.1% had sarcopenia. In Adjusted Model 2, the occurrence of sarcopenia was found to be significantly associated with a higher NHHR in cancer (95% confidence interval [CI]:1.01-1.39, P = 0.036). Individuals with high a NHHR had a 2.09-fold higher risk of developing sarcopenia in comparison to those with a low NHHR (95% CI:1.12-3.92, P = 0.022). RCS analysis further identified a U-shaped non-linear relationship between females with cancer and the muscle index. Subgroup analysis indicated that sex was a significant stratifying factor, whereas age, race, marital status, smoking and drinking habits, and history of cardiovascular disease, arthritis, hypertension, and diabetes had no significant impact. From the perspective of lipid metabolism, the NHHR may serve as an indicator for monitoring and preventing the occurrence of sarcopenia in individuals with cancer, particularly for females with cancer who appear to have greater sensitivity.